Volatile organic compound emission from holm oak infested by gypsy moth larvae: evidence for distinct responses in damaged and undamaged leaves - Staudt, Michael; Lhoutellier, Louise (Tree Physiology, 2007)
Foliage of Quercus ilex L. (holm oak), a widespread Mediterranean species, constitutively emits large quantities of a complex genotype-dependent mixture of volatile organic compounds (VOCs). During a mass outbreak of gypsy moth (Lymantria dispar L.) in southern France, we examined the effects of gypsy moth feeding on VOC production from whole apices and single leaves of Q. ilex. Feeding induced the emission of new VOCs at rates up to 240 ng m−2 s−1 (16% of the total VOC release), which mainly consisted of sesquiterpenes, a homoterpene and a monoterpene alcohol. The new compounds were emitted after a delay of several hours following infestation and their production declined rapidly when caterpillars were removed. Undamaged leaves of infested trees emitted new VOCs, but with a different composition to those of damaged leaves and at lower rates. Neither caterpillars nor caterpillar excrement released VOCs. Emission of constitutive VOCs by undamaged leaves of infested trees temporary increased by up to 30%, whereas, in damaged leaves, they remained stable and decreased after some days when necrotic spots occurred around the feeding sites. In continuous light and at constant temperature, emissions of new VOCs showed a marked diurnal cycle, whereas those of constitutive VOCs did not. The results suggest that induced VOCs make a significant contribution to the atmospheric VOC load and may mediate trophic interactions. The observed differential local and systemic responses in composition, quantity and time courses of emissions mirror the existence of several regulation processes triggered by different signaling compounds and elicitors.
10.1093/treephys/27.10.1433
Keywords: biogenic volatile organic compounds; biosphere atmosphere interactions; herbivores; homoterpene; Lymantria dispar; Monoterpene; plant defense; Quercus ilex; sesquiterpene; wounding

Herbivore dunging and endozoochorous seed deposition in a Mediterranean dehesa - Malo, J E; Jimenez, B; Suarez, F (JOURNAL OF RANGE MANAGEMENT, 2000)
Spatial patterns of herbivore defecation within grazing systems are important as they directly affect pasture growth and composition. These effects are partially linked to seed dispersal in dung, a little studied process. This paper focuses on: (1) quantification of dung and seeds deposited by herbivores in a Mediterranean grazing system, and (ii) analysis of the spatial variability of dung and seeds deposited within and among plant communities. We carried out year-long monthly quantifications of the depositions of rabbit (Oryctolagus cuniculus), fallow deer (Dama dama), red deer (Cervus elaphus), and cow (Bos taurus) dung to 32 plots distributed in Quercus rotundifolia Lam. and Fraxinus angustifolia Vahl woodlands, mixed scrub, and Cistus ladanifer L. scrub. We also quantified the germinable seed content of dung. The results revealed differences (p < 0.05) in dung deposition, varying (i) among the 4 species, (ii) within species (except for the red deer) among plant communities, and (iii) within plant communities. An average of 735 seeds/m(2) were returned to the soil via dung, with the highest numbers in open woodlands (870-1,888 seeds/m(2)) and the lowest numbers in scrubs (83-315 seeds/m(2)). Cows dispersed the most seeds (68%), followed by red deer (20%), rabbits (7%), and fallow deer (5%). Spatial variability in deposition led to accumulations of up to several thousand seeds at points covered by the dung. The effect of seed input to the seed bank and on vegetation may be low at large and medium-sized spatial scales, but it can be very important at small scales and for colonization processes.
Keywords: dispersal; dung; endozoochory; herbivores; Mediterranean pastures; Spatial pattern

Herbivore dunging and endozoochorous seed deposition in a Mediterranean dehesa - Malo, J. E.; Jimenez, B.; Suarez, F. (JOURNAL OF RANGE MANAGEMENT, 2000)
Spatial patterns of herbivore defecation within grazing systems are important as they directly affect pasture growth and composition. These effects are partially linked to seed dispersal in dung, a little studied process. This paper focuses on: (1) quantification of dung and seeds deposited by herbivores in a Mediterranean grazing system, and (ii) analysis of the spatial variability of dung and seeds deposited within and among plant communities. We carried out year-long monthly quantifications of the depositions of rabbit (Oryctolagus cuniculus), fallow deer (Dama dama), red deer (Cervus elaphus), and cow (Bos taurus) dung to 32 plots distributed in Quercus rotundifolia Lam. and Fraxinus angustifolia Vahl woodlands, mixed scrub, and Cistus ladanifer L. scrub. We also quantified the germinable seed content of dung. The results revealed differences (p < 0.05) in dung deposition, varying (i) among the 4 species, (ii) within species (except for the red deer) among plant communities, and (iii) within plant communities. An average of 735 seeds/m(2) were returned to the soil via dung, with the highest numbers in open woodlands (870-1,888 seeds/m(2)) and the lowest numbers in scrubs (83-315 seeds/m(2)). Cows dispersed the most seeds (68%), followed by red deer (20%), rabbits (7%), and fallow deer (5%). Spatial variability in deposition led to accumulations of up to several thousand seeds at points covered by the dung. The effect of seed input to the seed bank and on vegetation may be low at large and medium-sized spatial scales, but it can be very important at small scales and for colonization processes.
The following values have no corresponding Zotero field: pub-location: 445 UNION BLVD, STE 230, LAKEWOOD, CO 80228-1259 USA publisher: SOC RANGE MANAGEMENT
Keywords: dispersal; dung; endozoochory; herbivores; Mediterranean pastures; Spatial pattern

LAS BOÑIGAS DE VACA, EL ENCESPEDADO DE POA BULBOSA, Y LA DIVERSIDAD EN UN PASTIZAL DE DEHESA - Malo, J E Juan E; Suarez, F; Vaca, L A S Boñigas D E; Poa, E L Encespedado D E; Diversidad, Y L A; Un, E N; Dehesa, Pastizal D E (Pastos, 1996)
The interactions of cattle dung pats, the Poa bulbosa Turf and the number of species in a pasture is analyzed at a 10x10 cm scale, through a four-year monitoring of 50 dung pats. Dung pats elimínate the Poa bulbosa Turf, and its recovering takes more than four years. The rest of the species are also displaced by dung pats, but they colonize the gaps much faster. Thus, the number of species by sample is significantly smaller on dung pats the first year after deposition (5-4 vs. 10-8), not distinguishable the second and third years (9-2 vs. 10-0 and 9-3 vs. 8-0), and significantly higher the fourth year after depo- sition (13-8 vs. 10-7). These results seem to be associated to the competitive behaviour of Poa bulbosa. This species colonizes the gaps slowly, but it is able to displace other species from them. The effect of the process is relatively small for the whole pasture due to the small área covered by dung pats. However, due to the uneveness of dung deposi- tion it can contribute to the development of pasture gradients of composition and diver- sity associated to grazing.
Keywords: Central Spain; centro de españa; competencia; competition; dinámica de pastizales; disturbance; dung; excrementos; herbivores; herbívoros; pasture dynamics; perturbación